Redesigning a Participatory Health Study for a French Industrial Context. (November 2016) - Allen, Barbara L.; Cohen, Alison K.; Ferrier, Yolaine; Lees, Johanna; Richards, Travis
The Marseille, France, metropolitan area is home to a heavily concentrated industrial region directly adjacent to residential communities. These towns have been subjected to a wide variety of social science and public health studies, but residents continue to have many questions about health concerns for which they currently have primarily anecdotal evidence. Reflecting on our in-progress research in two of these towns, we argue that community-based participatory research that draws from both social science and public health science can be successfully adapted to the French political and cultural context and is key for developing environmental health research that is relevant for community residents and local leaders. Understanding and working within the customs of the local values and practices culture is critical for community-based participatory research regardless of location but is particularly paramount when working in non-United States contexts, since local values and practices will shape the particular techniques used within the community-based participatory research framework.